Nutritional knowledge, attitude and practices of mothers regarding vegetable oil consumption in rural and urban areas of Oyo-State, Nigeria - Farinola- Udofia, Florence Adetutu; Adaramoye, Toyin Olanike; Sulaiman, Mariam Eniola; Fadupin, Grace Fadupin T (World Nutrition, 2025)
Background Vegetable oils play a crucial role as part of family nutrition as a primary food source for fat for consumption, flavor, and nutrient absorption. Knowledge gaps on handling, quality, and health effects exist, however, particularly among mothers, and they play the primary role as family-level decision-makers for nutrition. Mothers’ knowledge on vegetable oils’ consumption as part of KAP (knowledge, attitude, and practice) was crucial for enabling effective public health action and dietary interventions. Objective This study assessed mothers’ knowledge, attitudes, and practices regarding vegetable oil consumption in rural and urban Oyo State, Nigeria. Methods This descriptive, cross-sectional study employed a multistage sampling technique. Structured questionnaires were used to ascertain socioeconomic characteristics, level of knowledge, attitude, and practices regarding vegetable oil consumption. Descriptive and inferential statistical tests, conducted using version 16.0 of the SPSS software, ascertained differences as well as relationships. Results There were significant differences in the knowledge and practices of urban and rural respondents. Unhealthy behavior was prevalent, with 68.5% of respondents reusing vegetable oil for frying and 57.3% bleaching their oil before consumption. Education level and income level had a strong correlation with knowledge and appropriate consumption practices for oils (p < 0.05). Conclusions Nutrition education is necessary for increasing safe consumption of vegetable oil, especially among rural households. Encouragement through campaigns on quality consciousness, health risks of poor handling, and the impact of dietary fat intake on a long-term basis is necessary.